Feasibility of methylated ctDNA detection in plasma samples of oropharyngeal squamous cell carcinoma patients. Issue 11 (20th July 2020) - de Jesus, Lais Machado; dos Reis, Mariana Bisarro; Carvalho, Raiany Santos; Scapulatempo Neto, Cristovam; de Almeida, Gisele Caravina; Laus, Ana Carolina; Marczynski, Gabriella Taques; Leal, Leticia Ferro; Melendez, Matias Eliseo; de Marchi, Pedro; Manuel Reis, Rui; Carvalho, André Lopes; et al.
Abstract: Background: Oropharyngeal squamous cell carcinomas (OpSCCs) are commonly associated with high rates of treatment failure. Objectives: To evaluate methylation‐based markers in plasma from OpSCC patients as emerging tools for accurate/noninvasive follow‐up. Methods: Pretreatment formalin‐fixed paraffin‐embedded (FFPE) biopsies (n = 52) and paired plasma (n = 15) were tested for the methylation of CCNA1, DAPK, CDH8, and TIMP3 by droplet digital PCR (ddPCR). Results: Seventy‐one percent (37/52) of the biopsies showed methylation of at least one of the evaluated genes and tumor CCNA1 methylation was associated with recurrence‐free survival. Methylated circulating tumor DNA (meth‐ctDNA) was detected in 11/15 (73.3%) plasma samples; conversely, plasma samples from healthy controls were all negative for DNA methylation (area under the curve = 0.867; 95% confidence interval = 0.720‐1.000). Additionally, preliminary results on the detection of meth‐ctDNA in plasma collected during follow‐up closely matched patient outcome. Conclusions: The results suggest the feasibility of detecting meth‐ctDNA in plasma using ddPCR and a possible application on routine setting after further validation.